Progresi Karir Akuntan: Tinjauan Literatur Sistematis Mengenai Hambatan Gender dan Keterkaitannya dengan Intervensi Organisasi - Muthi’a Handayani; Aspahani; Tamiimah Mufiidah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This systematic literature review aims to comprehensively analyze research findings related to career progression in the accounting profession. Although the representation of women in the accounting profession continues to increase globally, various studies indicate that equality in career progression and access to leadership positions has not yet been fully achieved. Therefore, this review seeks to synthesize existing empirical evidence to identify the main factors influencing the differences in career paths between male and female accountants. The method used in this study is the Systematic Literature Review. The SLR approach was chosen for its ability to provide a systematic, transparent, and replicable process in identifying, evaluating, and synthesizing all research relevant to the formulated research question. Through strict selection and analysis procedures, previous studies were reviewed to obtain a comprehensive overview of the dynamics of accountants' career progression. The review results indicate that career progression in the accounting profession is a complex and multidimensional process, influenced by the interaction of structural, organizational, cultural, and individual factors. Factors such as a masculine organizational culture, family responsibility burdens, limited access to mentoring and professional networks, as well as work policies that are not always gender-sensitive, have been shown to contribute to the stagnation of women's careers. Although various equality initiatives have been implemented, significant gender disparities still persist, particularly at the managerial and leadership levels. Based on these findings, this review highlights the research gaps and proposes future research directions to promote a more inclusive and fair working environment in the accounting profession.